THE POLICY MODEL OF DIGITAL-BASED MICRO-BUSINESS ASSISTANCE FOR ECONOMIC RECOVERY DURING THE PANDEMIC - Lukmanul Hakim (Faculty of Law, Universitas Lampung, 2021)
Micro-businesses have an essential role in driving an economic revival in Indonesia. However, they are particularly vulnerable during the pandemic. The COVID-19 pandemic has significantly impacted the long-term viability of micro, small, and medium-sized enterprises (MSMEs) in the financing, production, distribution, and market demand. This paper argues that an assistance policy model for micro-businesses accelerating the economy during a pandemic is needed. It also raises the question of how government policies in developing micro-businesses. The library method, which relied on secondary data, was used to conduct the research. The result suggests that the ideal assistance model policy for MSMEs in accelerating the regional economy is by using platform-based digital technology so that the flexibility of purchasing raw materials to sales can be integrated into one and reach all consumers around the world. Government policies in developing MSMEs in the new normal era include launching the National Economic Recovery Program, as mandated by Government Regulation Number 23 of 2020, implementing stimulus programs for MSMEs such as interest subsidies and restructuring.